PENERAPAN INTERNET OF THINGS PADA SISTEM KONTROL PENERANGAN RUMAH BERBASIS WEB APPLICATION MENGGUNAKAN METODE LOGIKA FUZZY - Eko Lesmana; Nurhayati Nurhayati (STMIK KAPUTAMA, 2020)
The need for electrical energy in everyday life is so important, improper and uncontrolled use can result in waste. Efforts to create energy-efficient homes need to start from simple things such as the use of lights, often forgetting to turn off the light switch when going out of the house or problems, especially in setting the brightness of the house lights, fuzzy logic provides an alternative solution. Fuzzy logic is a smart method that is appropriate for mapping a parameter input space into an output space for the brightness adjustment action of a lamp to light dimly, medium and bright. Efforts that can be made to deal with the problems above certainly require an intelligent control system with smart methods such as fuzzy logic and can be controlled remotely in order to overcome the existing problems. One concept that is popular right now is the Internet of Things (IoT), the development of IoT is a concept that aims to expand the benefits of internet connectivity that is connected continuously. IoT has capabilities such as data sharing, remote control, and so on. In building a control system by applying the IoT concept, a platform that supports that concept is also needed, NodeMCU a microcontroller which is equipped with a wifi module for microcontroller communication to the internet, so that the microcontroller can be used to apply the IoT concept in controlling home lights remotely, such as turning on the remote and turn off and adjust the brightness of the home lights with the fuzzy logic method intelligence.